Conflicts of language: Language, a Pandora’s Box - González González, Miguel Alberto (Rastros Rostros, 2012)
This reflection paper stems from the research project “The languages of power”, developed at the Universidad de Manizales in 2010. It is a discussion about language, its logic, its organization and the acting of people while in the communication process, which can generate conflict. Therefore, to question the role of language and its responsibility in the birth of conflicts is the main purpose of this essay, it is a venture to take out humanity’s conflicts on language itself. This look, if anything, encourages us to keep thinking and researching the functions, retreats, deployments and missions of languages.
Keywords: conflict; language; thinking; reality; meaning